Efektivitas Media Pembelajaran Plickers terhadap Pemahaman Materi Pendidikan Al Islam Siswa SMK (Deskripsi Data, Uji Normalitas, Uji Homogenitas, Uji Independent Sample T-test, dan Uji N-Gain) - Siti Rohani; Harisatunisa Harisatunisa (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research examines how much Plickers, as a technology-driven educational tool, enhances the comprehension of Islamic Education topics among eleventh-grade learners at SMK Muhammadiyah 1 Purwokerto. The study arose from two main issues identified in the classroom: the inadequate understanding of Al Islam content among students and their minimal engagement levels, both of which were partially linked to the ongoing dependence on traditional, teacher-led teaching methods. A quantitative approach was utilized, employing a quasi-experimental design featuring a non-equivalent control group structure. Sixty students took part, with one group (XI TJKT 1) receiving instruction supported by Plickers while the other group (XI TJKT 2) experienced standard learning techniques. Data from pre-tests and post-tests were collected and then evaluated through normality assessments, homogeneity checks, Independent Sample T-Test, and N-Gain score calculations, all processed via SPSS software. The findings indicated a statistically significant difference in the post-test results of the two groups, with a significance level (Sig. 2-tailed) of 0.027, which is less than 0.05. The average post-test score for the experimental group was 79.427, exceeding the control group’s score of 74.177. In terms of learning progress, the experimental group had an average N-Gain Score of 0.5365 (53.65%), while the control group scored 0.5160 (51.60%). Although both groups were in the moderate improvement range, the experimental group demonstrated consistently higher progress, confirming that Plickers is effective in enhancing students' understanding of Islamic Education topics. Keywords: Learning Effectiveness, Learning Media Plickers, Student Comprehension